Hyperbole in poetry: A case study of exaggeration - Muhammad, Manal Jasim (Opción, 2020)
The present study identifies the linguistic means used to realize hyperbole in poetry as a rhetorical device that makes readers experience the beauty of poetic language. To achieve the aim of the study, a model of analysis in accordance with Spitzbardt (1963), Norrick (1982), and McCarthy & Carter (2004) is used. The analysis of data under investigation reveals that hyperbole is a crucial aid used by poets to portrait the real world as imaginative. In conclusion, poets prefer using lexico-grammatical repertoires than lexico-grammatical configurations.